2018
DOI: 10.1111/tpj.14144
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase GCN5 contributes to cell wall integrity and salt stress tolerance by altering the expression of cellulose synthesis genes

Abstract: Summary Excess soluble salts in soil are harmful to the growth and development of most plants. Evidence is emerging that the plant cell wall is involved in sensing and responding to salt stress, but the underlying mechanisms are not well understood. We reveal that the histone acetyltransferase General control non‐repressed protein 5 (GCN5) is required for the maintenance of cell wall integrity and salt stress tolerance. The levels of GCN5 mRNA are increased in response to salt stress. The gcn5 mutants exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 74 publications
3
80
0
Order By: Relevance
“…The first HMT recruiters in Arabidopsis are the members of the BBR/BPC family, that were shown to be responsible for establishing the silencing mark [67,68]. As another common type of histone modification-histone acetylation-is reversible and dynamically maintained by the antagonistic action of histone acetyltransferases (HATs) and histone deacetylases (HDACs) [56,69]. It is generally realized that the acetylation neutralizes the positive charge of lysine side chains on histones and reduces its interaction with the negatively charged DNA backbone, and thus relax the chromatin structure and promote gene transcription [70,71].…”
Section: Histone Modificationmentioning
confidence: 99%
See 3 more Smart Citations
“…The first HMT recruiters in Arabidopsis are the members of the BBR/BPC family, that were shown to be responsible for establishing the silencing mark [67,68]. As another common type of histone modification-histone acetylation-is reversible and dynamically maintained by the antagonistic action of histone acetyltransferases (HATs) and histone deacetylases (HDACs) [56,69]. It is generally realized that the acetylation neutralizes the positive charge of lysine side chains on histones and reduces its interaction with the negatively charged DNA backbone, and thus relax the chromatin structure and promote gene transcription [70,71].…”
Section: Histone Modificationmentioning
confidence: 99%
“…Previous studies revealed that various HATs and HDACs modulate plant gene expression in response to environmental stresses in wheat and barley. For instance, TaGCN5, a wheat ortholog of Arabidopsis histone acetyltransferases AtGCN5, plays an important role in regulating wheat defense response to heat and salt stresses (Table 1) [56,57]. The expression of TaGCN5 was induced by treatment with heat and salt in bread wheat (Table 1) [56,57].…”
Section: Histone Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Blue arrows indicate the directionality of transcription. Line graphs display the transcriptional changes after wounding and error bars indicate the standard deviation (n = 3 independent experiments) dynamic than methylation 62 and it is involved in various stress and hormonal responses [63][64][65][66][67] . Our data therefore support the view that acetylation-mediated transcriptional modification is a general mechanism to swiftly respond to environmental or endogenous cues.…”
Section: Discussionmentioning
confidence: 99%